(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2013)
Mimosa belongs to the taxonomic group Magnoliopsida and family Mimosaseae. In Latin it is called as Mimosa pudica Linn. Ayurveda has declared that its root is bitter, acrid, cooling, vulnerary, alexipharmic. It is used in the treatment of leprosy, dysentery, vaginal and uterine complaints, and inflammations, burning sensation, asthma, leucoderma, fatigue and blood diseases. Decoction of root is used as gargle to reduce toothache. It is very useful in diarrhea (athisaara), amoebic dysentery (raktaatisaara), bleeding piles and urinary infections. This review gives a brief compilation of its phytochemical and pharmacological activities.